Green protocol for the synthesis of N-oxides from secondary amines using vanadium silicate molecular sieve catalyst - Phukan, P.; Khisti, R. S.; Sudalai, A. (Journal of Molecular Catalysis A-Chemical, 2006)
Vanadium silicate molecular sieve catalyst VS-I was found to promote efficiently the oxidation of alpha alpha,alpha'alpha'-tetrasubstituted secondary amines with 30% aqueous hydrogen peroxide as oxidant. In comparison to other catalysts reported to date, this heterogeneous catalyst offers a remarkably simple workup procedure and is reusable without any appreciable loss of activity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heterogeneous catalyst; Hydrogen peroxide; N-oxide; VS-1; zeolite

Transesterification of cyclic carbonates with methanol at ambient conditions over tungstate-based solid catalysts - Sankar, M.; Nair, C. Madhavan; Murty, K. V. G. K.; Manikandan, Palanichamy (Applied Catalysis A-General, 2006)
Dimethyl carbonate synthesis with 80 mol% yield is achieved through transesterification of ethylene carbonate with methanol at ambient conditions (RT and atmospheric pressure) using alkali and alkaline-earth tungstates as solid catalysts. The catalysts are efficient even at the sub-ambient temperatures. Reactions under CO2 pressure indicate that CO2 atmosphere retards the transesterification reaction completely below 100 degrees C. Experimental conditions of 150 degrees C and 3.4 MPa CO2 pressure are required to obtain maximum DMC yield of 71 mol%. Synthesis of DMC by one-pot synthesis using epoxide, CO2 and methanol is not as effective as that by two-step method with the present catalyst system. Raman and IR spectra of methanol-interacting tungstates indicate the formation of a methoxide ion species adsorbed at the catalyst surface as one possible reaction intermediates. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Dimethyl carbonate; ethylene carbonate; heterogeneous catalyst; Raman spectroscopy; sodium tungstate; transesterification

Efficient N-arylation of amines catalyzed by Cu-Fe-hydrotalcite - Jadhav, Vinod H.; Dumbre, Deepa K.; Phapale, Vilas B.; Borate, Hanumant B.; Wakharkar, Radhika D. (Catalysis Communications, 2007)
An efficient N-arylation of amines with aryl halides in presence of heterogeneous recyclable Cu-Fe-hydrotalcite catalyst has been developed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: amines; Aryl halides; Cu-Fe-hydrotalcite; heterogeneous catalyst; N-arylation

Transesterification of alpha-haloesters and beta-ketoesters over Mg-Al-hydrotalcites (HT)-like anionic clays - Bulbule, Vivek J.; Borate, Hanumant B.; Munot, Yogesh S.; Deshpande, Vishnu H.; Sawargave, Sangmeshwer P.; Gaikwad, Abaji G. (Journal of Molecular Catalysis A-Chemical, 2007)
Transesterification of alpha-haloesters was achieved by reaction of alcohols in the presence of Mg-Al-HT-like anionic clays. beta-Ketoesters were also transesterified under similar conditions on reaction with alcohols with a wide variety of functional groups. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alpha-haloesters; beta-ketoesters; heterogeneous catalyst; Hydrotalcites; transesterification

Synthesis of substituted styrenes and stilbenes mediated by palladium on zirconia - Borate, Hanumant B.; Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Journal of Chemical Research-S, 2008)
Palladium on zirconia has been found to be an effective catalyst for the synthesis of various substituted styrenes and stilbenes, including biologically active natural products, by reaction of aryl halides with olefins.
Keywords: heterogeneous catalyst; palladium on zirconia; stilbenes; styrenes

Scolecite as an efficient heterogeneous catalyst for the synthesis of 2,4,5-triarylimidazoles - Gadekar, Lakshman S.; Mane, Shivshankar R.; Katkar, Santosh S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2009)
Natural scolecite has been found as an effective catalyst for the one-pot synthesis of 2,4,5-triarylimidazole derivatives via a three component reaction using benzil or benzoin, aldehydes and ammonium acetate. This method provides several advantages such as being environmentally benign, reusable, possessing high yields with increased variations of the substituents in the product and preparative simplicity.
Keywords: 2; 4; 5-Triarylimidazoles; heterogeneous catalyst; Three-component reaction

Scolecite catalyzed facile and efficient synthesis of polyhydroquinoline derivatives through hantzsch multi-component condensation - Gadekar, Lakshman S.; Katkar, Santosh S.; Mane, Shivshankar R.; Arbad, Balasaheb R.; Lande, Machhindra K. (Bulletin of the Korean Chemical Society, 2009)
A facile and efficient synthetic route has been developed for the polyhydroquinoline via four component reactions of aldehydes, dimedone, ethyl acetoacetate and ammonium acetate in the presence of catalytic amount of scolecite in ethanol at 70 degrees C through Hantzsch reaction. This method gives remarkable advantages such as simple work-up procedure. environmentally friendly, inexpensive, non-toxic and recyclable catalyst, shorter reaction time along with excellent yields
Keywords: heterogeneous catalyst; Multicomponent reaction; Polyhydroquinoline; Reusable catalyst

Transesterification of sunflower oil catalyzed by flyash-based solid catalysts - Kotwal, M. S.; Niphadkar, P. S.; Deshpande, Suvarna S.; Bokade, Vijay V.; Joshi, P. N. (Fuel, 2009)
Flyash-based base catalyst was used in the transesterification of sunflower oil with methanol to methyl esters in a heterogeneous manner. Catalyst preparation variables such as, the KNO(3) loading amount and calcination temperature were optimized. The catalysts were characterized by powder XRD. The catalyst prepared by loading of 5 wt.% KNO(3) on flyash followed by its calcination at 773 K has exhibited maximum oil conversion (87.5 wt.%). The influence of various reaction parameters such as % catalyst loading, methanol to oil molar ratio, reaction time, temperature, reusability of the catalyst on the catalytic activity was investigated. K(2)O derived from KNO(3) might be an essential component in the catalyst for its efficiency. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Flyash; heterogeneous catalyst; Methyl ester; Sunflower oil; transesterification

H-beta zeolite: an efficient, reusable catalyst for one-pot synthesis of isatins from anilines - Raj, I. Victor Paul; Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Acta Chimica Slovenica, 2010)
We describe a simple and highly efficient procedure for the single-step preparation of isatins from the commercially available anilines using H-beta zeolite as a truly heterogeneous catalyst. H-beta zeolite is readily separated from reaction mixture by simple filtration and reused several times without considerable loss of activity.
Keywords: Anilines; H-beta zeolite; heterogeneous catalyst; isatins

Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide

ZnO-beta zeolite: as an effective and eco-friendly heterogeneous catalyst for the synthesis of benzothiazole derivatives - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Vidhate, Kaluram N.; Lande, Machhindra K. (Chinese Chemical Letters, 2010)
A cheap and recyclable ZnO-beta zeolite was used as catalyst for the synthesis of benzothiazole derivatives. This method provides several advantages such as environmental friendliness, short reaction times, high yields, simple work-up procedure and catalyst was successfully reused for four cycles without significant loss of activity. (C) 2009 Machhindra K. Lande. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Benzothiazole; cyclocondensation; heterogeneous catalyst; ZnO-beta zeolite

ZnO-beta zeolite: as an effective and reusable heterogeneous catalyst for the one-pot synthesis of polyhydroquinolines - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Green Chemistry Letters and Reviews, 2010)
ZnO-beta zeolite, an inexpensive and mild catalyst, has been used for the synthesis of polyhydroquinolines in excellent yields from the one-pot four-component condensation of aldehydes, dimedone, ethyl acetoacetate, and ammonium acetate in ethanol at room temperature. The remarkable advantages offered by this method are a green catalyst, mild reaction conditions, simple work-up procedures, much faster reactions, and excellent yield of products. Furthermore, the catalyst could be reused several times keeping its initial activity in recycled reactions.
Keywords: Hantzsch condensation; heterogeneous catalyst; multicomponent; ZnO-beta zeolite

Selective catalytic oxidation of geraniol to citral with molecular oxygen in supercritical carbon dioxide - Dapurkar, Sudhir E.; Kawanami, Hajime; Chatterjee, Maya; Rode, Chandrasekhar V.; Yokoyama, Toshirou; Ikushima, Yutaka (Applied Catalysis A-General, 2011)
Selective catalytic oxidation of geraniol to citral with molecular oxygen in supercritical carbon dioxide (scCO(2)) has been investigated. The catalyst used was a chromium containing mesoporous molecular sieve catalyst viz. CrMCM-41. Comparison studies were performed with CoMCM-41. PtMCM-41 and PdMCM-41 catalysts. Among the various catalysts studied. CrMCM-41 showed a high conversion of geraniol and an excellent selectivity for citral. In contrast CoMCM-41, PtMCM-41 and PdMCM-41 catalysts exhibited low conversion of geraniol. However all three catalysts compared showed similar citral selectivity to CrMCM-41. The effect of CO(2) pressure and reaction temperature geraniol oxidation was studied with CrMCM-41. Supercritical CO(2) medium was found to enhance the conversion of geraniol and/or yield of citral. It was noticed that the catalyst can be recycled with negligible loss of conversion. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Citral; Geraniol; heterogeneous catalyst; Molecular oxygen; Selective oxidation; Supercritical carbon dioxide

Selective hydrogenation of chloronitrobenzenes with an MCM-41 supported platinum allyl complex derived catalyst - Indra, Arindam; Rajamohanan, Pattuparambil R.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2011)
A platinuin precatalyst (1) has been prepared by reacting [(eta(3)-C3H5)(4)Pt4Cl4] with surface functionalized MCM-41 with pendant -(CH2)(3)NH(CH2)(2)NH2 groups. For the hydrogenation of o-, m- and p-chloronitrobenzenes to the corresponding chloroanilines, 1 is found to be a highly active catalyst with good selectivities for them-and p-isomers. Its performance is superior to that of its palladium analogue and far superior to that of commercial (5%) Pt/C or (5%) Pt/Al2O3. Comparison of solid state and solution NMR data and other evidences indicate that on treatment with the functionalized MCM-41 support; [(eta(3)-C3H5)(4)Pt4Cl4] loses the ally! ligand. XPS data show that in the fresh catalyst Pt is present in the 2+ oxidation state. Based on these and analytical data, co-ordination by surface diamine and hydroxo groups to Pt2+ in 1 is suggested. In the used catalyst both Pt2+ and Pt are present but the amount of metallic platinum is similar to 16% of the total. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chloronitrobenzenes; Dehydrohalogenation; heterogeneous catalyst; MCM-41; Selective hydrogenation

Synthesis of 2,5-furandicarboxylic acid by the aerobic oxidation of 5-hydroxymethyl furfural over supported metal catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Reaction Kinetics Mechanisms and Catalysis, 2014)
Supported Pt catalysts are synthesized, characterized and are used in the liquid phase air oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). Under the optimum reaction conditions of a stepwise increase in the reaction temperature (75 and 140 degrees C for 12 h each), we achieved as high as 96 % FDCA yield in presence of 1 bar oxygen pressure over Pt/c-Al2O3. It is shown that as the oxygen pressure increases (1-10 bar), the FDCA yields decrease, since at higher partial pressure of oxygen, overoxidation reactions of substrate and product(s) are possible. It is interesting to note that even with air as an oxidant, we obtained similar yields of FDCA as that with oxygen. Moreover, the effects of base (weak or strong), its concentration (equimolar or excess) were studied in detail. It is important to increase the reaction temperature in a stepwise manner to achieve higher yields of FDCA since at higher temperatures HMF undergoes self-degradation and thus the yields of FDCA decrease. The self-degradation of HMF is also proved by undertaking the reaction under nitrogen environment. The study on the effect of substrate-to-catalyst ratio is done to improve up on the economics of overall process. The effect of supports (reducible and non-reducible) and their oxygen storage capacity is discussed and is proposed to be one of the factors to change the course of reaction. Furthermore, we have shown that FDCA formed in the reaction can be successfully isolated (91 %, isolated yield) in the pure form and its purity is confirmed by NMR, melting point, and elemental analysis. The catalysts were characterized with X-ray powder diffraction, transmission electron microscopy and inductively coupled plasma-optical emission spectroscopy techniques.
Keywords: Biomass; FDCA; green chemistry; heterogeneous catalyst; HMF; Impregnation; Oxidation

Tailor made ionic liquids: catalyst and media for organic transformations - Chandra, Prakash; Shinde, Sandip S.; Biradar, Ankush V. (Current Organic Chemistry, 2015)
Ionic liquids are considered as one of the safe, green and environmentally benign solvents/catalysts for many organic reactions. Particularly, imidazolium based ionic liquids attracted much attention in basic as well as applied research. The major role of these ionic liquids is the replacement of the existing corrosive solvents, which are largely used in most of the organic processes and make these processes more eco-friendly. Recent report reveals the importance of imidazolium based ionic liquids, supported on silica gel or polystyrene in catalysis. The solid supports have well versed properties such as easy anchoring of ionic liquid, chemically and mechanically very stable and inert in nature. These ionic liquids can be tailored either by covalent attachment or simple deposition of the ionic liquid on the surface of the support. Both approaches showed enhanced reactivity and selectivity for various reactions. In this review, we made an attempt to review the recent reports related to synthesis and applications of tailor made ionic liquids and their use as catalyst in Aldol, Friedel-Crafts alkylation, hydroformylation, nucleophilic substitution and biomass transformation reactions.
Keywords: Green solvent; heterogeneous catalyst; organic transformation; sustainable process; task-specific ionic liquids

Ru(II)-functionalized SBA-15 as highly chemoselective, acid free and sustainable heterogeneous catalyst for acetalization of aldehydes and ketones - Lazar, Anish; Betsy, K. J.; Vinod, C. P.; Singh, A. P. (Catalysis Communications, 2018)
Combining electron deficient Ru(II) coordination sites with organofunctionalized SBA-15, (L)Ru(Il)@SBA-15, result in a mild, neutral, water scavenger free and chemo-selective acetalization catalyst for cyclic/acyclic acetals. Vacant coordination sites of ruthenium in (L)Ru(II)@SBA-15 activates protecting groups as well as reactants simultaneously and restricts the reverse acetalization reaction. Synthesized (L)Ru(Il)@SBA-15 catalyst has been thoroughly characterized and act as competitive catalyst compared to conventional acid catalysts. (L) RuaD@SBA-15 performs high catalytic activity as well as selectivity within 20 min with high TOF. The catalyst can be recycled and reaction parameters are optimized.
Keywords: Acetalization reactions; Acid free; chemo-selective; heterogeneous catalyst; Reusable; Ru(II) immobilized SBA-15

Bentonite - Clay - supported cuprous iodide nanoparticles (BENT- CuI NPs): a new heterogeneous catalyst in diversity - oriented synthesis of 1, 2, 3-triazoles in aqueous medium - Chavan, V, Pramod; Charate, Shrinivas P.; Desai, V, Uday; Rode, V, Chandrashekhar; Wadgaonkar, Prakash P. (Chemistryselect, 2019)
Bentonite clay supported cuprous iodide nanoparticles (BENT-CuI NPs) were prepared and demonstrated for the first time as an efficient heterogeneous catalyst in diversity oriented, green synthesis of 1,2,3-triazoles by one-pot, three component reaction between alkyl halides, arylboronic acids, or epoxides with alkynes and sodium azide in aqueous medium. The catalyst was characterized by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), Energy Dispersive X-ray Spectroscopy(EDS), Scanning Electron Microscopy (SEM), X-Ray Powder Diffraction (XRD), Transmission Electron Microscopy (TEM) as well as Brunauer-Emmett-Teller (BET) techniques and was found to be reusable for five consecutive runs without significant loss of activity.
Keywords: 1; 2; 3-triazoles; arylboronic acids; click synthesis; epoxides; green chemistry; heterogeneous catalyst

Selective and robust Ru catalyst for the aqueous phase aerobic oxidation of furfural to 2-furoic acid - Lokhande, Priya; Dhepe, Paresh L. (ACS Applied Materials & Interfaces, 2023)
Synthesis of 2-furoic acid (FURA) via oxidation of furfural (FAL) is vital in evolving the biorefinery concept as FURA has numerous important applications in the pharmaceuticals and optic areas. Though few works on this reaction are done, those are marred with shortcomings such as the nonrecyclability of catalyst, dilute solutions, lower yields, or use of H2O2 as an oxidizing agent. Herein, we report catalytic aqueous phase oxidation of FAL to FURA using molecular oxygen as an oxidizing agent. For the synthesis of FURA, various catalysts with a combination of metal (Pt, Pd, Ru) and supports (carbon, Al2O3) were prepared and characterized by multiple techniques (X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), X-ray photoelectron spectroscopy (XPS)). Oxidation of FAL carried out over 5 wt % Ru/C catalyst in the presence of Na2CO3 yielded 83% of FURA at 120 degrees C and 15 bar oxygen pressure. The catalyst could show potential for reusability as similar activity was achieved after subjecting the spent catalyst to mild reduction treatment (150 degrees C). Studies on the effects of temperature, pressure, and time could help accomplish enhanced yields of FURA. Additionally, learning about the effect of base (weak/strong/solid) revealed that due to the weak basicity of Na2CO3, higher yields could be achieved by maintaining approximately a pH of 11, which is optimal for suppressing side reactions. Under the given conditions, FURA is stable (>90%) and also adsorption studies divulge that it is immediately removed from the catalyst surface, and hence higher yields could be achieved in our catalytic system. Using the initial rates methodology, an activation energy of 21.91 kJ mol(-1) was derived and also a high turn over frequency (TOF) (85.9 h(-1)) was observed under optimized conditions.
Keywords: 2-furoic acid (FURA); Biomass conversion; furfural (FAL); heterogeneous catalyst; Oxidation; ruthenium on carbon etc

Selective oxidation of 5-HMF to DFF over alkali promoted Mn nanocomposite - Solanki, Bhanupratap Singh; Roh, Hyun-Seog; V. Rode, Chandrashekhar (Applied Catalysis A-General, 2023)
Various compositions of Cs promoted Mn catalysts were synthesized and investigated for selective oxidation of 5HMF to DFF, among which Mn-Cs(80:20) was found to be most efficient giving 91 % conversion of 5-HMF and 99 % selectivity to DFF. Detail characterization like N2-sorption, BET surface area, TG-DTA, XRD, XPS, FE-SEM-EDX, TEM, HR-TEM, CO2-TPD, H2-TPR, O2-TPO, FTIR, Raman spectra and CH3OH-IR were done to establish structureactivity correlation. Enhanced surface area, porosity, thermal stability, dual morphologies were observed due to inclusion of Cs in Mn lattice domain which further enhanced the crystallinity, and oxygen diffusion on the surface. Mixed morphologies comprising nanoparticles (4-5 nm) and nanocubes (50-60 nm) were observed with enhanced redox potential and reduced work function due to weakening of Mn-O bonds. Significant increase in the basicity of catalyst, interfacial redox properties and lattice oxygen led to highly efficient oxidation of 5-HMF to DFF via Mars-van Krevelen mechanism at relatively milder conditions i.e. T = 90 degrees C and PO2= 200 psig. The catalyst was easily recyclable up to 7 times with minor loss in activity which was regenerated heat treatment protocol.
Keywords: 5-HMF; Biomass; heterogeneous catalyst; polyurethane; Selective oxidation

Ferric oxide nanocatalyst: synthesis, characterization, and application in the one-pot three-component synthesis of 3,4,5-trisubstituted isoxazole derivatives - Totre, Ganesh; Shinde, Dnyaneshwar; Shirsath, Sachin; Patil, Prakash; Kulkarni, Pramod (Monatshefte Fur Chemie, 2024)
In this study, we have focused on the preparation and application of a nano-ferric oxide catalyst as a heterogeneous catalyst in the one-pot, three-component synthesis of isoxazole derivatives. The ferric oxide catalyst was synthesized using a simple precipitation method and thoroughly characterized using techniques such as FT-IR, XRD, SEM, EDX, and BET. The effectiveness of the ferric oxide catalyst as a heterogeneous catalyst was investigated in the synthesis of 3,4,5-trisubstituted isoxazole. The results of the synthesis demonstrated that the catalyst exhibited high efficiency in facilitating the three-component, one-pot synthesis of 3,4,5-trisubstituted isoxazole derivatives. The synthesis route employed in this study offers several advantages, including its simplicity, ease of workup, and environmental friendliness. Furthermore, the catalyst was successfully recovered and reused for five cycles without experiencing a significant loss in catalytic activity. This finding highlights the excellent stability and promising potential of the catalyst for organic transformations. Overall, our study showcases the successful preparation and application of the nano-ferric oxide catalyst in the synthesis of isoxazole derivatives, providing valuable insights into its catalytic performance and potential for future applications in organic chemistry.
Keywords: Ferric oxide nanoparticles; heterogeneous catalyst; Isoxazole; Multicomponent reaction

Novel sulfonic acid functionalized silica supported isonicotinic acid catalyst for conversion of 2-methylfuran to diesel fuel precursors - Tarade, Komal P.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (Catalysis Letters, 2024)
Polyfuranic compounds produced after carbon up-gradation of 2-methylfuran by acid catalyzed C-C bond forming reactions when undergo hydro-deoxygenation produce diesel fuel. Herein, we prepared a simple and novel silica supported sulfonic acid functionalized isonicotinic acid SO3H-INA@SiO2 catalyst by treating isonicotinic acid with chlorosulphonic acid followed by heterogenization on silica. This heterogeneous solid acid catalyst was explored for the solvent free conversion of 2-methylfuran to diesel fuel precursors of C-15 and C-20 units via tandem ring opening followed by condensation sequence. Under optimized reaction conditions, SO3H-INA@SiO2 was able to convert, 2-methylfuran completely into condensation products such as 5,5-bis(5-methylfuran-2-yl)pentan-2-one (1) and 2,4,4-tris(5-methylfuran-2-yl)pentan-1-ol (2) with 19% and 67% yields, respectively. The heterogeneous SO3H-INA@SiO2 catalyst was successfully recycled up to six consecutive runs without loss of its activity. The SO3H-INA@SiO2 catalyst offered superior activity as compared to the commercially available -SO3H functionalized resins. Superior activity of the prepared catalyst could be attributed for its higher acidity, smaller particle size and high surface area. Structure of the prepared catalyst was confirmed by FTIR and solid state NMR. Total acidity of the prepared catalyst was determined by acid-base titration.
Keywords: 2-Methylfuran; Diesel fuel; heterogeneous catalyst; Ionic solid; solid acid